Horizontal Transmission of Hepatitis B Virus From Mother to Child Due to Immune Escape Despite Immunoprophylaxis. Issue 5 (May 2019) - Kanji, Jamil N.; Penner, Robert E.D.; Giles, Elizabeth; Goodison, Karin; Martin, Steven R.; Marinier, Eric; Osiowy, Carla
Abstract : ABSTRACT: Hepatitis B virus (HBV) vaccination starting at birth is approximately 95% effective in preventing mother-to-child transmission to infants born to HBV-infected mothers. A higher risk of transmission is associated with birth to a highly viremic mother, often due to transplacental exposure, while later horizontal transmission is much less common, particularly following complete vaccination. This study reports a case of infection in an older child despite appropriate immunoprophylaxis starting at birth and an apparent protective immune response post-vaccination. Two immune escape mutations within the antigenic determinant of the surface antigen-coding region were observed in the child's dominant HBV sequence, whereas the maternal HBV variant lacked mutations at both sites. Ultra-deep sequencing confirmed the presence of 1 mutation at low levels within the maternal HBV quasispecies population, suggesting early exposure to the child followed by viral evolution resulting in immunoprophylaxis escape and chronic infection. Abstract : Supplemental Digital Content is available in the text